Piperazinyl pyrophosphate flame retardant and preparation method thereof
By modifying the surface silanes in the pyropipezine phosphate powder and adding carbon nanotubes to the phase change polymer, combined with polydopamine coating, the problem of surface coating uniformity of piperazine pyrophosphate-based flame retardant is solved, and its resistance is improved Fuel performance and compatibility simplify the preparation process.
Patent Information
- Application Number
- CN202411856246.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The surface coating materials of piperazine pyrophosphate-based flame retardant have problems in terms of uniformity, which affects its flame retardant effect and compatibility.
The surface silane modification of piperazine pyrophosphate powder and ultrasonic dispersion in ethanol was added to form a composite precursor, then impregnated in phase change polymer, and finally polydopamine coating on the surface of the composite intermediate , piperazine pyrophosphate-based flame retardant was prepared.
The flame retardant properties of flame retardant and compatibility in polymers are improved, the preparation process is simplified, complex equipment is avoided, and structural stability and mechanical properties are enhanced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardants, and in particular to a piperazine pyrophosphate flame retardant and a preparation method thereof. Background Art
[0002] With the rapid development of modern industry, polymer materials have been widely used in various fields. However, most polymer materials are flammable, which largely limits their use in some fields with high fire safety requirements, such as electronics, construction, and transportation. Therefore, the research and development and application of flame retardants used in polymer materials have become a key link in ensuring the safety of materials. Traditional flame retardants include halogen flame retardants, which have significant flame retardant effects, but they produce a large amount of toxic and harmful gases during the combustion process, causing serious harm to the environment and human health.
[0003] With the increasing awareness of environmental protection and the improvement of relevant laws and regulations, halogen-free flame retardants have gradually become a hot spot for research and development. Among them, piperazine pyrophosphate flame retardant, as a halogen-free flame retardant, has received widespread attention due to its unique structure and excellent flame retardant properties. Piperazine pyrophosphate flame retardant is usually synthesized by chemical reaction of piperazine and pyrophosphate and other raw materials. Its molecular structure contains functional groups such as piperazine ring and pyrophosphate ester. The piperazine ring has certain rigidity and stability and can provide structural support, while the pyrophosphate ester can decompose at high temperature, thereby inhibiting the spread of flames.
[0004] Chinese invention patent with publication number CN117777546A discloses a method for preparing a piperazine pyrophosphate halogen-free flame retardant, which comprises reacting piperazine with disodium dihydrogen pyrophosphate and coating nanoparticles after surface modification; and Chinese invention patent with publication number CN117126458A discloses a method for preparing a piperazine pyrophosphate-based flame retardant, which comprises reacting an alkaline solution in a mixed aqueous solution of a composition of piperazine pyrophosphate and melamine polyphosphate and a metal salt to form a piperazine pyrophosphate-based flame retardant coated with a metal hydroxide.
[0005] The preparation method in the above prior art aims to improve the flame retardant effect and thermal stability of the flame retardant and improve the compatibility of the flame retardant in polymer materials by surface treatment of the piperazine pyrophosphate-based flame retardant. However, the uniformity of the coating of nanoparticles and metal hydroxides and other modified materials on the surface of piperazine pyrophosphate seriously affects its comprehensive performance, so it is urgent to provide a solution to improve the above problems. Summary of the invention
[0006] The object of the present invention is to provide a piperazine pyrophosphate-based flame retardant and a preparation method thereof. The provided method has a simple process and can uniformly coat the piperazine pyrophosphate matrix and the coating material on the surface without using complex equipment, thereby improving the flame retardancy and compatibility of the prepared flame retardant.
[0007] In a first aspect, the present invention provides a method for preparing a piperazine pyrophosphate-based flame retardant, comprising: performing surface silane modification on piperazine pyrophosphate powder to obtain modified powder; ultrasonically dispersing the modified powder in ethanol to obtain a mixed suspension, and adding carbon nanotubes to the mixed suspension to perform ultrasonic dispersion, followed by separation and drying to obtain a composite precursor; impregnating the composite precursor in a phase change polymer to obtain a composite intermediate; and coating the surface of the composite intermediate with polydopamine to obtain the piperazine pyrophosphate-based flame retardant.
[0008] The preparation method provided by the present invention can synergistically improve the flame retardant performance of the flame retardant by compounding piperazine pyrophosphate with a phase change polymer, and can effectively improve the compatibility of the flame retardant in the high molecular polymer after coating the outer side with polydopamine. In addition, the preparation method provided by the present invention has a simple process, and can uniformly coat the piperazine pyrophosphate matrix and the coating material on the surface without using complex equipment, so as to improve the flame retardancy and compatibility of the prepared flame retardant.
[0009] Optionally, when the piperazine pyrophosphate powder is subjected to surface silane modification, the average particle size of the piperazine pyrophosphate powder is 5 μm-10 μm.
[0010] Optionally, when the piperazine pyrophosphate powder is subjected to surface silane modification, the piperazine pyrophosphate powder is immersed in a silane solution, wherein the silane solute in the silane solution is 3-aminopropyltriethoxysilane.
[0011] Optionally, when the modified powder is ultrasonically dispersed in ethanol, the solid-liquid ratio of the modified powder to the ethanol is 0.05 g / mL-0.08 g / mL.
[0012] Optionally, when the modified powder is ultrasonically dispersed in ethanol, the modified powder is ultrasonically treated in ethanol at a frequency of 20 kHz to 30 kHz.
[0013] Optionally, when the modified powder is ultrasonically dispersed in ethanol, the modified powder is ultrasonically treated in ethanol for 10-15 min.
[0014] Optionally, when the modified powder is ultrasonically dispersed in ethanol, the modified powder is ultrasonically dispersed in ethanol at 30°C-40°C.
[0015] Optionally, when the carbon nanotubes are added to the mixed suspension, the mass ratio of the carbon nanotubes to the modified powder is 1:(5-8).
[0016] Optionally, the carbon nanotubes include single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0017] Optionally, the carbon nanotubes are added to the mixed suspension and ultrasonically dispersed at 20 kHz-30 kHz.
[0018] Optionally, the carbon nanotubes are added to the mixed suspension for ultrasonic dispersion, and then separated and dried at 60°C-80°C.
[0019] Optionally, the carbon nanotubes are added to the mixed suspension for ultrasonic dispersion and then separated by suction filtration or filtration.
[0020] Optionally, the carbon nanotubes are added to the mixed suspension for ultrasonic dispersion, and then the solids obtained by separation are separated and washed.
[0021] Optionally, when the composite precursor is impregnated in a phase change polymer, the phase change polymer includes one of a phase change polyolefin and a phase change wax.
[0022] Optionally, when the composite precursor is impregnated in the phase change polymer, the mass ratio of the composite precursor to the phase change polymer is 1:(0.2-0.3).
[0023] Optionally, when impregnating the composite precursor in the phase change polymer, the composite precursor is vacuum impregnated in the phase change polymer.
[0024] Optionally, when the composite precursor is impregnated in the phase change polymer, the composite precursor is preheated in a vacuum environment at 80° C.-100° C.
[0025] Optionally, when polydopamine is coated on the surface of the composite intermediate to obtain the piperazine pyrophosphate based flame retardant, the method includes: ultrasonically dispersing the composite intermediate and the dopamine aqueous solution to obtain a precursor suspension; adding Tris-HCl solution dropwise to the precursor suspension and stirring for reaction, and then separating and drying to obtain the piperazine pyrophosphate based flame retardant.
[0026] Optionally, the mass ratio of the composite intermediate to dopamine in the dopamine aqueous solution is 1:(0.05-0.15).
[0027] Optionally, the composite intermediate and the dopamine aqueous solution are ultrasonically dispersed at 40°C-50°C.
[0028] Optionally, the concentration of the Tris-HCl solution is 1-5 mol / L.
[0029] Optionally, the pH of the Tris-HCl solution is 8.5.
[0030] Optionally, the Tris-HCl solution is added dropwise for 60-100 min.
[0031] In a second aspect, the present invention also provides a pyrophosphate piperazine-based flame retardant prepared by any of the above-mentioned optional preparation methods, comprising a pyrophosphate piperazine matrix and a carbon nanotube coating layer coated on the surface of the pyrophosphate piperazine matrix, wherein the carbon nanotube coating layer is impregnated with a phase change polymer, and the outer side of the carbon nanotube coating layer is coated with a polydopamine layer, and the polydopamine layer encapsulates the phase change polymer.
[0032] The preparation method of the piperazine pyrophosphate flame retardant provided by the present invention has at least one of the following beneficial effects compared with the prior art: 1. The flame retardant properties of flame retardants can be effectively improved by using piperazine pyrophosphate and phase change polymer in combination; 2. By coating the surface of piperazine pyrophosphate powder with carbon nanotubes, the carbon nanotubes can form a carbon nano skeleton on the surface of piperazine pyrophosphate, which can accommodate the phase change polymer and also play a role in skeleton support, effectively improving the structural stability of the flame retardant after being dispersed in the high molecular polymer; 3. By coating the outermost layer of the flame retardant with a polydopamine layer, the compatibility of the flame retardant in the polymer can be improved to avoid affecting the mechanical properties of the polymer, and the structural stability of the flame retardant in the polymer can be further improved. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0034] The present invention provides a method for preparing a piperazine pyrophosphate flame retardant, comprising: S1, performing surface silane modification on piperazine pyrophosphate powder to obtain modified powder; S2, ultrasonically dispersing the modified powder in ethanol to obtain a mixed suspension, adding the carbon nanotubes to the mixed suspension, ultrasonically dispersing the carbon nanotubes, and then separating and drying to obtain a composite precursor; S3, impregnating the composite precursor into a phase change polymer to obtain a composite intermediate; S4. Polydopamine is coated on the surface of the composite intermediate to obtain a pyrophosphate piperazine-based flame retardant.
[0035] In fact, after the surface of the piperazine pyrophosphate powder is modified with silane during step S1, silane can react with the active groups on the surface of the piperazine pyrophosphate powder and introduce organic functional groups on its surface by chemical bonding, thereby improving the coating and bonding effects of carbon nanotubes on the surface of the piperazine pyrophosphate in step S2.
[0036] Specifically, the average particle size of the piperazine pyrophosphate powder used in step S1 is 5 μm-10 μm. In fact, the use of piperazine pyrophosphate powder with a small particle size is conducive to improving the dispersion effect when performing surface silane modification, and its larger specific surface area is conducive to uniform modification of its surface. At the same time, after the flame retardant is prepared, the piperazine pyrophosphate powder with a small particle size can be more evenly dispersed in the polymer and form a flame retardant network structure therein, thereby comprehensively improving the flame retardant properties and mechanical properties of the polymer material.
[0037] In some embodiments, in step S1, the piperazine pyrophosphate powder is immersed in a silane solution to perform surface silane modification on the piperazine pyrophosphate powder. Specifically, the silane solute in the silane solution used is 3-aminopropyltriethoxysilane. In fact, the immersion in the silane solution is conducive to the silane solution to fully infiltrate the surface of the piperazine pyrophosphate powder, thereby improving the modification effect and uniformity.
[0038] Specifically, in step S1, the piperazine pyrophosphate powder is ultrasonically dispersed in a silane solution in a water bath environment at 50° C.-60° C. This can improve the modification effect by accelerating the modification rate in a heated environment, and at the same time, the ultrasonic cavitation effect can be used to remove tiny bubbles attached to the surface of the piperazine pyrophosphate powder, and avoid the piperazine pyrophosphate powder from agglomerating and settling in the silane solution.
[0039] In some embodiments, when the piperazine pyrophosphate powder is surface-modified in the silane solution in step S1, the mass ratio of the piperazine pyrophosphate powder to the silane solute in the silane solution is 1:(0.05-0.08). In addition, the solvent in the silane solution can be one of methanol and ethanol. In fact, the solvent in the silane solution can be an organic solvent commonly used in the art, which is necessary to be able to dissolve the silane solute and not react with piperazine pyrophosphate.
[0040] In fact, when performing step S2, the modified powder is ultrasonically dispersed in ethanol, which is not only conducive to the uniform dispersion of the modified powder to form a uniform mixed suspension, but also can heat and volatilize the ethanol in the subsequent drying process, thereby avoiding residues in the prepared composite precursor. In addition, after the carbon nanotubes are added to the mixed suspension in step S2, since the pyrophosphate piperazine powder is silane-modified in advance in step S1, the carbon nanotubes can be attached to the surface of the modified powder and intertwined, entangled, and interspersed to form a carbon nanotube coating layer, thereby protecting the pyrophosphate piperazine therein.
[0041] In some embodiments, the solid-liquid ratio in the mixed suspension obtained after ultrasonically dispersing the modified powder and ethanol in step S2 is 0.05 g / mL-0.08 g / mL. In fact, by controlling the solid-liquid ratio in the mixed suspension, it is beneficial for the modified powder to maintain a good dispersion state in the mixed suspension, avoid agglomeration and sedimentation, and it is also beneficial for the carbon nanotubes to be uniformly loaded on the surface of the modified powder after the carbon nanotubes are added later.
[0042] In some embodiments, in step S2, the modified powder is ultrasonically treated in ethanol at 30°C-40°C at a frequency of 20kHz-30kHz for 10-15min. In fact, ultrasonic treatment at 30°C-40°C can promote the contact between ethanol and the surface of the modified powder, and at the same time can activate the active functional groups and carbon nanotubes on the surface of the modified powder, thereby facilitating the composite treatment of carbon nanotubes and modified powder. At the same time, by controlling the ultrasonic frequency and the duration of ultrasonic treatment, it is possible to avoid excessive ultrasonic damage to the internal structure of the modified powder and to avoid affecting the bonding strength between the pyrophosphate piperazine powder and the carbon nanotube coating.
[0043] In some embodiments, after adding the carbon nanotubes to the mixed suspension in step S2, the mass ratio of the added carbon nanotubes to the modified powder is 1:(5-8). In fact, by controlling the amount of carbon nanotubes and modified powder, the coating thickness of the carbon nanotubes on the surface of the modified powder can be adjusted, so that the carbon nanotubes and the modified powder can be well coordinated, avoiding the carbon nanotube coating thickness being too large to affect the flame retardant properties of the flame retardant, and avoiding the carbon nanotube coating thickness being too small to affect the mechanical properties of the flame retardant and the subsequent capacity of the phase change polymer.
[0044] In some embodiments, the carbon nanotubes used in step S2 include single-walled carbon nanotubes and multi-walled carbon nanotubes. In fact, single-walled carbon nanotubes are seamless nanoscale tubular structures formed by curling a single layer of carbon atoms, and have a high aspect ratio and can be used as reinforcing fibers to effectively improve the mechanical properties of the flame retardant itself and the polymer to which the flame retardant is added, while multi-walled carbon nanotubes are composed of multiple layers of concentric carbon nanotubes, which can form a complex carbon nano network after being compounded with the modified powder. Specifically, the carbon nanotubes used can be commercially available products or conventionally synthesized in the laboratory.
[0045] In some embodiments, after adding the carbon nanotubes to the mixed suspension in step S2, ultrasonic dispersion is performed at an ultrasonic frequency of 20kHz-30kHz, which is conducive to the uniform dispersion of the carbon nanotubes and the modified powder and thus achieves a uniform coating treatment of the two. In addition, after the ultrasonic dispersion is performed, the solid is separated by suction or filtration, and the solid is rinsed with deionized water and dried in an oven at 60°C-80°C to constant weight.
[0046] In fact, after the composite precursor is impregnated in the phase change polymer in step S3, the phase change polymer can penetrate into the interior of the carbon nanotube coating on the surface of the composite precursor. Since the phase change polymer can undergo phase change during the temperature change process, it can absorb heat to delay the temperature rise and prevent heat transfer in the combustion area. It can not only have a flame retardant effect, but also fill the pore structure in the carbon nanotube coating, further improving the density and structural stability of the flame retardant.
[0047] In some embodiments, the phase change polymer used in step S3 includes one of phase change polyolefin and phase change paraffin. Specifically, the number average molecular weight of the phase change polyolefin is 2000-4000. In fact, the phase change polymer can use a commercially available conventional product, such as ExxonMobil TM LLDPE LL 1004YB (phase transition temperature is 150°C).
[0048] Specifically, in step S3, the mass ratio of the composite precursor to the phase change polymer is 1:(0.2-0.3). This helps to fully impregnate the phase change polymer on the surface of the composite precursor, and can effectively increase the loading amount of the composite precursor on the phase change polymer, thereby effectively filling the pores on the surface of the composite precursor, and synergistically improving the flame retardant properties of the flame retardant. In fact, the composite precursor can be preheated in a vacuum environment at 80°C-100°C, which is conducive to breaking the closed pores on the surface of the composite precursor, thereby increasing the loading amount of the phase change polymer, and then vacuum impregnating the composite precursor in the phase change polymer, which is conducive to improving the impregnation effect.
[0049] In fact, after the composite intermediate is surface-coated with polydopamine in step S4, a protective layer can be formed on the surface of the composite intermediate, thereby improving the overall stability and anti-aging performance of the flame retardant, and at the same time, it can also improve the interfacial bonding force of the flame retardant in the polymer, thereby improving the structural stability and positional stability of the flame retardant in the polymer, thereby effectively improving the flame retardant performance.
[0050] In some embodiments, when executing step S4, the steps include: ultrasonically dispersing the composite intermediate and the dopamine aqueous solution to obtain a precursor suspension; dropping a Tris-HCl solution dropwise into the precursor suspension and stirring the solution for reaction, and then separating and drying the solution to obtain a pyrophosphate piperazine-based flame retardant. In fact, ultrasonically dispersing the composite intermediate and the dopamine aqueous solution in advance is beneficial for pre-dispersing the composite intermediate and dopamine, and using the ultrasonic cavitation effect to remove tiny bubbles adhering to the surface of the composite intermediate, which is beneficial for the dopamine aqueous solution to fully infiltrate the surface of the composite intermediate, and by dropping the Tris-HCl solution, dopamine is promoted to undergo a self-polymerization reaction on the surface of the composite intermediate, thereby forming a polydopamine layer.
[0051] In some embodiments, in step S4, the mass ratio of the composite intermediate to dopamine in the dopamine aqueous solution is 1:(0.05-0.15). In fact, by controlling the amount of the composite intermediate and dopamine, the coating thickness and coating uniformity of the polydopamine layer on the surface of the composite intermediate can be effectively adjusted. In addition, the composite intermediate and the dopamine aqueous solution can be ultrasonically dispersed at 40°C-50°C, which is conducive to the self-polymerization reaction of dopamine. In fact, in step S4, the concentration of the Tris-HCl solution is 1mol / L-5mol / L, the pH is 8.5, and the dripping time of the Tris-HCl solution is controlled to be 60min-100min.
[0052] Example 1
[0053] This embodiment 1 provides a method for preparing a piperazine pyrophosphate flame retardant, comprising the following steps: S1. Add piperazine pyrophosphate powder with an average particle size of 10 μm into an ethanol solution of 3-aminopropyltriethoxysilane (KH550), control the mass ratio of piperazine pyrophosphate powder to 3-aminopropyltriethoxysilane to be 1:0.05, and ultrasonically disperse it at a frequency of 20 kHz in a 55°C water bath environment for 10 minutes and then keep it warm for 10 minutes, filter under reduced pressure and rinse the obtained solid with deionized water, and then dry it in a vacuum drying oven at 50°C to constant weight to obtain a modified powder; S2, adding the modified powder into anhydrous ethanol at a solid-liquid ratio of 0.06 g / mL, and ultrasonically treating the mixed suspension at a frequency of 20 kHz for 15 min in a 35°C water bath environment, adding multi-walled carbon nanotubes (purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, model TNMH0) into the mixed suspension, controlling the mass ratio of multi-walled carbon nanotubes to modified powder to be 1:6, and ultrasonically treating the mixed suspension at a frequency of 20 kHz for 10 min in a 55°C water bath environment, filtering and separating under reduced pressure, rinsing the obtained solid with deionized water, and drying the mixed suspension in a vacuum drying oven at 70°C to constant weight to obtain a composite precursor; S3, preheat the composite precursor in a vacuum environment at 90℃ for 1h, and then TM LLDPE and LL1004YB phase change polyolefin were mixed at a mass ratio of 1:0.2, immersed in a vacuum environment for 5 hours, filtered and separated, and then cooled to room temperature to obtain a composite intermediate; S4. The composite intermediate and the dopamine aqueous solution are ultrasonically mixed at a frequency of 20 kHz for 10 minutes in a 45°C water bath environment to obtain a precursor suspension, and a Tris-HCl solution with a concentration of 1 mol / L and a pH of 8.5 is added dropwise into the precursor suspension, and the dripping time of the Tris-HCl solution is controlled to be 80 minutes. After vacuum filtration and washing of the precipitate, it is dried at 50°C to constant weight to obtain a pyrophosphate piperazine-based flame retardant; wherein the mass ratio of the composite intermediate to dopamine is 1:0.1, and the mass ratio of the amount of Tris-HCl in the Tris-HCl solution to dopamine is 1:3.
[0054] Example 2
[0055] This embodiment 2 provides a method for preparing a piperazine pyrophosphate flame retardant, which is different from the embodiment 1 in that in step S3, phase change paraffin wax (purchased from Shanghai Joule Wax Co., Ltd., model 140, phase change temperature 140°C) is used to replace ExxonMobil TM LLDPE LL 1004YB phase change polyolefin, and the mass ratio of the composite precursor to the phase change paraffin is 1:0.2.
[0056] Example 3
[0057] This Example 3 provides a method for preparing a pyrophosphate piperazine-based flame retardant, which is different from Example 1 in that single-walled carbon nanotubes (purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, model number TNSRH) are used to replace multi-walled carbon nanotubes in step S2, and the mass ratio of single-walled carbon nanotubes to modified powder is 1:6.
[0058] Comparative Example 1 This comparative example 1 provides a method for preparing a piperazine pyrophosphate-based flame retardant, which is different from Example 1 in that step S1 is not performed, and in step S2, piperazine pyrophosphate powder with an average particle size of 10 μm is directly added to anhydrous ethanol at a solid-liquid ratio of 0.06 g / mL, and the mass ratio of multi-walled carbon nanotubes to piperazine pyrophosphate powder is controlled to be 1:6.
[0059] Comparative Example 2 This comparative example 2 provides a method for preparing a piperazine pyrophosphate flame retardant, which is different from Example 1 in that step S3 is not performed, and the composite precursor obtained in step S2 is directly mixed with the dopamine aqueous solution in step S4, and the mass ratio of the composite precursor to dopamine is controlled to be 1:0.1.
[0060] Comparative Example 3 This comparative example 3 provides a method for preparing a piperazine pyrophosphate-based flame retardant, which is different from Example 1 in that step S4 is not performed, and the composite intermediate prepared in step S3 is the piperazine pyrophosphate-based flame retardant.
[0061] Comparative Example 4 This comparative example 4 provides a method for preparing a piperazine pyrophosphate-based flame retardant, which is different from Example 1 in that step S2 and step S3 are not performed, the modified powder prepared in step S1 is mixed with a dopamine aqueous solution in step S4, and the mass ratio of the modified powder to dopamine is controlled to be 1:0.1.
[0062] Performance Testing The piperazine pyrophosphate flame retardants prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were added to polypropylene resin to prepare flame-retardant polypropylene resin. The flame-retardant polypropylene resin includes the following components by mass: 60 parts of polypropylene 8101 (purchased from Sinopec Yanshan Petrochemical), 2 parts of maleic anhydride grafted polypropylene with a grafting rate of 1.5wt.%, 15 parts of piperazine pyrophosphate flame retardant, 4 parts of conductive carbon black, 1 part of calcium stearate, 0.5 parts of silane coupling agent KH-560, and 0.5 parts of antioxidant 1010; the preparation method of the flame-retardant polypropylene resin includes: mixing polypropylene 8101 and maleic anhydride grafted polypropylene at 70°C, then adding piperazine pyrophosphate flame retardant, conductive carbon black, calcium stearate, silane coupling agent KH-560 and antioxidant 1010, blending at 90°C, and performing melt blending and extrusion molding at 200°C.
[0063] The flame retardant polypropylene resins corresponding to Examples 1 to 3 and Comparative Examples 1 to 4 were tested for the following items, and the test results are shown in Table 1 below: Tensile yield strength, in MPa, based on standard ISO 527-2; Elongation at break, in %, based on standard ISO 527-2; Flame retardant performance, unit s, based on standard MT 113-1995, measuring the flaming burning time and flameless burning time under an alcohol burner.
[0064] Table 1 Performance test
[0065] As can be seen from Table 1, the addition of different phase change polymers in Example 1 and Example 2 has no significant effect on the mechanical properties of the flame retardant polypropylene obtained, but the flame retardant properties of the obtained flame retardant polypropylene are slightly reduced due to the slightly lower phase change temperature of the phase change paraffin wax, while the use of single-walled carbon nanotubes in Example 3 has no significant effect on the properties, only a slight decrease in mechanical strength. In addition, in Comparative Example 1, the surface modification of piperazine pyrophosphate powder was not performed, which affected the combination of piperazine pyrophosphate and carbon nanotubes, so its mechanical strength was reduced, and in Comparative Example 2, the impregnation of phase change polymer was not performed, which had a significant negative effect on the flame retardant properties, and in Comparative Example 3, the coating treatment of polydopamine was not performed, which affected the compatibility of the flame retardant in the flame retardant polypropylene resin and had a negative effect on the mechanical properties.
[0066] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A method for preparing a piperazine pyrophosphate flame retardant, characterized in that: include: The surface of piperazine pyrophosphate powder is modified by silane to obtain modified powder; The modified powder is ultrasonically dispersed in ethanol to obtain a mixed suspension, and carbon nanotubes are added to the mixed suspension for ultrasonic dispersion, followed by separation and drying to obtain a composite precursor; the composite precursor is impregnated in a phase change polymer to obtain a composite intermediate; and the surface of the composite intermediate is coated with polydopamine to obtain a pyrophosphate piperazine-based flame retardant.
2. The preparation method according to claim 1, characterized in that: When the surface of piperazine pyrophosphate powder is modified by silane, the method comprises: the average particle size of the piperazine pyrophosphate powder is 5 μm-10 μm; and / or the piperazine pyrophosphate powder is immersed in a silane solution, wherein the silane solute in the silane solution is 3-aminopropyltriethoxysilane.
3. The preparation method according to claim 1, characterized in that: When the modified powder is ultrasonically dispersed in ethanol, the process includes: the solid-liquid ratio of the modified powder to the ethanol is 0.05 g / mL-0.08 g / mL; and / or, the modified powder is ultrasonically treated in ethanol at a frequency of 20 kHz-30 kHz; and / or, the modified powder is ultrasonically treated in ethanol for 10-15 minutes; and / or, the modified powder is ultrasonically dispersed in ethanol at 30° C.-40° C.
4. The preparation method according to claim 1, characterized in that: When adding carbon nanotubes into the mixed suspension, the mass ratio of the carbon nanotubes to the modified powder is 1:(5-8); and / or the carbon nanotubes include single-walled carbon nanotubes and multi-walled carbon nanotubes.
5. The preparation method according to claim 1, characterized in that: Adding carbon nanotubes to the mixed suspension and dispersing them ultrasonically at 20kHz-30kHz; and / or, adding carbon nanotubes to the mixed suspension and dispersing them ultrasonically, separating them and drying them at 60°C-80°C; and / or, adding carbon nanotubes to the mixed suspension and dispersing them ultrasonically, separating them by suction or filtering; and / or, adding carbon nanotubes to the mixed suspension and dispersing them ultrasonically, separating them and washing the separated solids.
6. The preparation method according to claim 1, characterized in that: When the composite precursor is impregnated in the phase change polymer, it includes: the phase change polymer includes one of phase change polyolefin and phase change paraffin; and / or, the mass ratio of the composite precursor to the phase change polymer is 1:(0.2-0.3); and / or, the composite precursor is vacuum impregnated in the phase change polymer; and / or, the composite precursor is preheated in a vacuum environment at 80°C-100°C.
7. The preparation method according to claim 1, characterized in that: When polydopamine is coated on the surface of the composite intermediate to obtain the piperazine pyrophosphate flame retardant, the method comprises: ultrasonically dispersing the composite intermediate and the dopamine aqueous solution to obtain a precursor suspension; dropwise adding a Tris-HCl solution to the precursor suspension and stirring the solution for reaction, and then separating and drying to obtain the piperazine pyrophosphate flame retardant.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the composite intermediate to dopamine in the dopamine aqueous solution is 1:(0.05-0.15); and / or, the composite intermediate and the dopamine aqueous solution are ultrasonically dispersed at 40° C.-50° C.
9. The preparation method according to claim 7, characterized in that: The concentration of the Tris-HCl solution is 1-5 mol / L; and / or the pH of the Tris-HCl solution is 8.5; and / or the dripping time of the Tris-HCl solution is 60-100 min.
10. A piperazine pyrophosphate flame retardant prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Piperazinyl pyrophosphate flame retardant, preparation method thereof and flame-retardant resin composition
CN117126458A
Piperazine pyrophosphate halogen-free flame retardant and preparation method thereof
CN117777546A
Polypiperazine phosphate composite flame retardant and preparation method thereof
CN111621021A
A polyamide ceramic composite nanofiltration membrane, its preparation method and its application
CN114931865A
Preparation method of microencapsulated core-shell structure coated piperazine pyrophosphate composite flame retardant
CN115010996A
Cited By
Migration-resistant piperazine pyrophosphate flame retardant and synthesis method thereof
CN120192590A